Antimicrobial Usage Surveillance Through Sales at Veterinary Drug Shops Intended for Livestock in Vietnam - Ha, Le Thi Thu; Rueanghiran, Chalalai; Giang, Nguyen Thi Huong; Thuy, Doan Phuong; Phu, Doan Hoang; Tuan Kiet, Bach; Hien, Vo Be; Hue, Le Thi; Padungtod, Pawin; Truong, Bao Dinh; Carrique-Mas, Juan J. (Frontiers in Sustainable Food Systems, 2021)
There is a pressing need to establish surveillance systems for antimicrobial use (AMU) intended for animal production particularly in many low- and middle-income countries. This is an extremely challenging task, notably due to the wide range of animal species, production types and antimicrobials available in the market. In Vietnam, farmers commonly buy antimicrobials from veterinary drug shops. Therefore, veterinary drug shops are a potential target for data collection on AMU. We collected antimicrobial sales data at veterinary drug shops and estimated the amount of AMU in different animal species by antimicrobial active ingredient (AAI) class using different measurement metrics. We compiled information on all antimicrobials licensed in Vietnam and used this information to develop a mobile application to capture sales of antimicrobials intended for use in poultry, pig, and ruminant. We provided tablets with this application to 60 veterinary drug shops in two provinces of the country (Bac Giang in the north, Dong Thap in the south; three districts and 30 shops per province) for data collection over 3 weeks. Total sales of antimicrobials were extrapolated to 1 year, and these amounts were related to three different denominator estimates in each province including standing animal body weight, animal biomass, and Population Correction Unit (PCU). A total of 3,960 transactions [2,577 (median 75.5 per shop) in Bac Giang; 1,383 (median 28.5 per shop) in Dong Thap] of 831 different antimicrobial-containing products were recorded in the 3-week period. Sales of 57 AAIs belonging to 17 classes were recorded. In the three Bac Giang districts, we estimated that 242.0 kg of AAI were hypothetically sold over 1 year. Of those, 202.2 kg (83.6%) were intended for poultry, 19.8 kg (8.1%) for pigs, and 20.0 kg (8.3%) for ruminants. In Dong Thap, an estimated 48.4 kg of antimicrobials were sold, including 28.9 kg (59.7%) for poultry, 16.0 kg (33.1%) for pigs, and 3.5 kg (7.2%) for ruminants. After standardized by different animal population denominators, AMU in Bac Giang amounted to 1129.2 mg/kg standing animal body weight, 480.2 mg/kg biomass, and 636.1 mg/kg PCU. In Dong Thap, AMU figures were 1211.0 mg/kg standing animal body weight, 595.8 mg/kg biomass and 818.5 mg/kg PCU. We discuss the observed differences between species, location and metrics, as well as the potential advantages and limitations (including potential sources of bias) of this methodology and its applicability at country level. Retail level data collection can effectively be integrated into AMU surveillance systems that help identify priority AMU management areas (species, regions, and antimicrobial classes), establish national benchmarks and reduction targets.